Rehabilitation of the traditional dwellings: a strategy for alleviating housing dilemma / Ziad Shehada, Naziaty Yaacob and Nila Keumal - Shehada, Ziad; Yaacob, Naziaty; Keumal, Nila (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
Ancient cities have a great cultural heritage in which the residential buildings form a proportion of up to 60%. These cities are characterised by meeting living population needs. However, the socio-economic and cultural developments occurred in the Palestinian society prompted many residents to abandon their traditional homes as they did not respond to the renewable community needs. The research aims to highlight the systematic rehabilitation of the heritage houses in Hebron old city (as a case study), and measure the satisfaction level of the residents through survey questionnaire. The research finds that traditional housing can meet the modern requirements through rehabilitation and achieves high degree of people s satisfaction.